VIDEO ILUSTRASI SEBAGAI MEDIA YANG MENGISAHKAN TENTANG “ PERJALANAN HIDUP SEBAGAI ANAK TULI “ - Leonita Gunawan; Carolus Astabrata; Irwan Harnoko (Penerbit dan Percetakan, CV. Picmotiv, 2023)
Abstract : Deaf children are children who do not have the ability to hear well so their way of communicating is different from hearing people. Video Documentation is a visual video work that tells real life stories or introduces certain topics with a factual approach through their activities, the reality of an event. Video documentation and illustrations are the result of imagination to convey information or official evidence in the form of writing, photos, videos, images for various purposes. Video documentation and illustrations are used as a reference for deaf children in writing short stories to tell about the journey of life as a deaf child and the real life that occurs in everyday life for deaf children. In general, deaf children experience difficulties in communicating verbally and hamper the development of their abilities. The role of video documentation aims to convey information about how to communicate with deaf children in verbal form and everyday sign language. This also helps to prove the abilities of deaf children to society to provide insight to the general public on how to communicate easily with deaf children. Apart from that, the development of video documentation and illustrations can help people in the process of learning to communicate directly with deaf children in making social adjustments.